2015
DOI: 10.1111/pin.12272
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic endothelial cancerization in papillary thyroid carcinoma: Hidden evidence of lymphatic invasion

Abstract: We hypothesize that cystic structures in metastatic papillary thyroid carcinoma (PTC) develop along the framework of lymphatic channels. To investigate this phenomenon, different categories of PTC were immunostained for D2-40 and TTF1. In this study, reactivity for D2-40 was considered as positive when there is membranous staining as often seen in lymphatic endothelial cells. Thirty cases of PTC with lymph node metastasis or with potential for lymphatic invasion and 20 cases metastatic PTC in lymph nodes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, CD31 labeling was not helpful for identifying the IN-like and destructive patterns because of partial or total loss of CD31 expression on the endothelial side of the venous wall. This loss of CD31 expression of endothelial labeling in cancer invasion foci was previously described in lymphatics of papillary thyroid carcinoma and was explained as endothelial cancerization [16]. Similarly, we also observed that CD31 expression was lost at the points at which the cancer-cell clusters attached to the intimal layer of Patients with pancreatobiliary tract cancer and venous invasion detected by H&E staining have significantly worse disease-free survival (3-year survival rate, 23%) than those without VI (46%; P = 0.016).…”
Section: Plos Onesupporting
confidence: 66%
“…However, CD31 labeling was not helpful for identifying the IN-like and destructive patterns because of partial or total loss of CD31 expression on the endothelial side of the venous wall. This loss of CD31 expression of endothelial labeling in cancer invasion foci was previously described in lymphatics of papillary thyroid carcinoma and was explained as endothelial cancerization [16]. Similarly, we also observed that CD31 expression was lost at the points at which the cancer-cell clusters attached to the intimal layer of Patients with pancreatobiliary tract cancer and venous invasion detected by H&E staining have significantly worse disease-free survival (3-year survival rate, 23%) than those without VI (46%; P = 0.016).…”
Section: Plos Onesupporting
confidence: 66%
“…Pathologic reassessment of 22 specimens including 13 L0, 2 L1, and seven tumors with no LVI documentation was performed by two independent, experienced pathologists. No cases showed LVI diagnosis according to the current definition [presence of tumor tissue and/or psammoma bodies in lymphatic spaces, including lymphatic spaces within the tumor, but also at the periphery of the tumor, or somewhere else in the resection specimen ( 29 )], despite nodal involvement. Two cases, which had originally been reported as L1 ( Supplementary Table 3 ), could not be confirmed as L1.…”
Section: Discussionmentioning
confidence: 95%
“…LVI (L-status; L1 = invasion and L0 = no invasion) is not regularly included in pathology reports in PTC in Europe, as it is not mandatory to report LVI according to the current TNM classification ( 28 ). One possible explanation is that LVI in PTC is often not easily identified in thyroid parenchyma ( Figure 1 ) ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L ymphatic vessels are the only pathway for lymphatic fluid to flow into venous bloodstream, and they are also one of the main channels for the migration and metastasis of malignant tumor cells [1]. Among the various neck malignancies, differentiated thyroid carcinomas (DTCs) are characterized by metastases to regional lymph nodes via lymphatic vessels [2,3]. Although high-frequency ultrasound imaging has become the first choice for examination and preliminary assessment of cervical lymph nodes, obviously its capacity of displaying the lymphatic vessels is still insufficient up to date [4].…”
mentioning
confidence: 99%